The Method of Determining the Limits of Possible Increase of Tariffs for Energy and Other Material Costs in the Sectors of the Economy of Republic of Moldova, Based on the Analysis of National Accounts - Postolaty V.M. (Problems of the Regional Energetics, 2016)
A method for calculating the limits of possible increase of tariffs for energy and other material costs in the sectors of the economy of Moldova, on the basis of the analysis of national accounts was elaborated. The analysis of macroeconomic indicators of the Republic of Moldova's economy for the period 2002-2014 was performed. The formulas that allow for practical calculations of allowable limits the possible establishment of tariffs for energy and other material costs to consumers at the stage of production and the end of its consumption with the use of national accounts were proposed. Proposals based on the fact that the real tariff increases should not exceed the growth of gross value added and real gross domestic product should be taken into account the purchasing power of consumers and the consumer price index.